Integrating the high peroxidase activity of carbon dots with easy recyclability: Immobilization on dialdehyde cellulose nanofibrils and cholesterol detection. (March 2022) - Bandi, Rajkumar; Alle, Madhusudhan; Dadigala, Ramakrishna; Park, Chan-Woo; Han, Song-Yi; Kwon, Gu-Joong; Kim, Jin-Chul; Lee, Seung-Hwan
Highlights: Fe, N-doped carbon dots (FeNCDs) with good fluorescence quantum yield and high peroxidase activity. Low km and high vmax values for both substrates and high specific activity of 3654 U/g. Immobilization of FeNCDs on dialdehyde cellulose nanofibrils via Schiff base reaction and reductive amination. Colorimetric detection of Cholesterol in human serum samples. High stability, easy recovery and reuse of nanozyme for up to 10 cycles. Abstract: Carbon dots (CDs) are widely explored as peroxidase mimics in recent times. However, low catalytic activity, substrate induced aggregation in the reaction medium and difficulties in recovery and reuse are the major hitches. A novel strategy is proposed here to circumvent these constrains by immobilizing amine functionalized, Fe, N-doped CDs (FeNCDs) with high peroxidase activity on dialdehyde cellulose nanofibrils (DACNF) via Schiff base reaction and reductive amination. FeNCDs with iron content of 5.37% and high peroxidase activity (specific activity of 3654 U/g) were prepared by simple hydrothermal reaction. FeNCDs exhibited a broad-spectrum peroxidase activity and steady-state kinetics revealed their better kinetic parameters (low Km and high Vmax ) over horseradish peroxidase (HRP) and Ping-Pong mechanism similar to HRP. Two fold increment in the peroxidase activity is observed under UV irradiation and mechanistic studies revealed the hydroxyl radical generation. DACNF with 1.25 ± 0.12 mM/g aldehyde content and 90% yield were produced by the periodate oxidation and served as an excellent matrix for FeNCDs to retain the fluorescence and peroxidase activities. Colorimetric assays based on 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) oxidation offered linear ranges of 10 – 80 µM and 50 – 400 µM and detection limits of 0.70 and 3.72 μM for H2 O2 and cholesterol respectively. The results of cholesterol detection in human serum samples were in well agreement with those of clinical laboratory. Further, the DACNF/FeNCDs nanohybrid presented a long shelf life and excellent reusability for 10 cycles. Fe content analysis by ICP-OES revealed the insignificant leaching of FeNCDs even after 10 cycles. As a whole, this stable and recyclable nanozyme with high catalytic activity presents a great promise for multiple applications including clinical diagnosis, environmental protection and antimicrobials. Graphical abstract:   Image, graphical abstract .